Pengaruh Pemberian Subtitusi Tepung Bulu Ayam Dengan Dedak Halus Terhadap Pertambahan Berat Badan Konsumsi Dan Efisiensi Pakan Sapi Aceh Jantan - Mahyuddin Mahyuddin (Jurnal Agripet, 2002)
ABSTRACT.Effect of substitution of feather meal by rise bran on body weight gains, feed consumption, and feed efficiency of the Aceh bullocks. The experiment was conducted at Lambaro Angan Kecamatan Darussalam. Four Aceh bullocks, 12 14 months old, with 140 160 kg weight were used as experiment materials. Experimental design of latin Square (4 x 4) with the treatments of 0 percent, 1 percent, 2 percent, 3 percent of feather meal were applied. The result showed that the feed consumption has no significant different (P 0.05), but the body weight gains, and feed efficiency were highly significant different (P 0.01). The used of 3 percent (0.6 kg) feather meal in the ration has increased body weight gains and feed efficiency more than other treatments.